Socio-cultural effects of Turkish tv series on Macedonian society : the cases of “Muhteşem Yüzyıl” and “Paramparça” - Nastoski, Nikola (My University, 2021)
Türkiye TV dizilerinin Makedon toplumu üzerindeki etkileri 2010 yılında Kuzey Makedonya’da yayınlanan ilk Türkiye dizisiyle başladı ve günden güne artıyor. Bu araştırma, bu etkilerin ne olduğunu, Makedon toplumunu nasıl etkilediğini ve bu etkilerin ne gibi değişiklikleri tetiklediğini belirleme amacını taşıyor. Bu araştırma için kullanılan yöntemler üç kategoriye ayrılmıştır. Birinci kategoride, araştırmacıyı ikinci kategoriye yönlendirecek olan Makedon toplumu üzerindeki ortak etki ve etkileri ortaya koyma amaçlı hazırlıksız görüşmeler yaptık. İkinci kategoride ise odak grubu ile yapılan derinlemesine görüşmeler araştırmacıyı, etkilerin verilerini sağlayacak anket araştırmasını üçüncü kategoriye yönlendirecektir. Bu araştırmanın sonuçları da kendi içinde iki kategoriye ayrılmıştır. İlk kategori, derinlemesine görüşmelerden elde edilen sonuçlar ve bunlar üzerinde yapılan analizlerdir. İkinci kategori ise anketten elde edilen bulgular ve bu bulgular üzerine yapılan analizlerdir. Bu araştırmanın sonucu, Türk dizilerinin etkilerinin mevcut olduğu kültür, dil, mutfak, tarih, ekonomi, moda ve turizm gibi Makedon toplumunun bazı alanlarında bazı etkileri tetikledikleri yönündedir.

The effects of Turkish TV series on Macedonian society are present since the first aired Turkish TV series in 2010, and from that moment onwards the effects are increasing. This research has the purpose to identify what these effects are and how they are influencing the Macedonian society and what kind of changes does this effects trigger. The methods used for this research are separated into three categories. In the initial category there were impromptu interviews that are meant to introduce the common effects and influences towards the Macedonian society that will lead the researcher to the second category. In the second category the in-depth interviews with the focus group will lead the researcher to the third category - the survey research that will provide the data for the effects. The results from this research are also divided into two categories. The first category are the results from the in-depth interviews and the analyses made on them. The second category are the findings from the survey and the analyses on these findings. The conclusion of this research is that the effects of Turkish TV series are present and that they are triggering some influences in several areas of the Macedonian society, like culture, language, cuisine, history, economy, fashion and tourism.
Keywords: Cuisine; Culture; Dil; Etkileri; Influences; Kültür; Language; Macedonia; Makedonya; Mutfak; Television serials, Turkish; Televizyon dizileri, Türk; Tourism; Turizmi TV series; Türk dizileri